Acid PAGE procedure for detection of phaseolins in field beans (Phaseolus vulgaris L.) - Hussain, A.; Espinel, MT; Roca, W.; Bushhuk, W (Springer, 1989)
A procedure based on acid polyacrylamide gel electrophoresis (acid PAGE) has been described. Resolution of phaseolin bands appears to be relatively superior to that obtained with basic PAGE system. The procedure discriminates S, T, C, M and B types of phaseolins; S, T and C have been reported previously while M and B types were identified in the present study.